Cultivo protegido de mudas de maracujá amarelo (Passiflora edulis Sims) em diferentes substratos com cama de Compost Barn e irrigadas com concentrações de água residuária doméstica tratada - Almeida, Romário de Sousa (2023)
The protected cultivation results in high productivity and quality to the cultures, being necessary the control of the micrometerological variables. The yellow passion fruit is one of the most cultivated fruit species in Brazil. The composition of the substrates is essential to ensure productivity, and the organic materials are sustainable alternatives. Regarding irrigation, water reuse is an option due to the presence of macro and micronutrients in the water. Thus, the objective of the present work was to evaluate the protected cultivation of yellow passion-fruit seedlings irrigated with concentrations of treated domestic wastewater in different formulations of substrates with Compost Barn bedding. The experiment was conducted in a double-arched greenhouse with a total area of 145.3 m2, oriented east-west and covered with 150 μm polyethylene film. The experimental design was entirely randomized, with five concentrations of treated domestic wastewater: CAR,0 (0% wastewater = AR); CAR,25 (25% AR + 75% AA = Supply water); CAR,50 (50% AR + 50% AA); CAR,75 (75% AR + 25% AA) and CAR,100 (100% AR) and five substrates: S70TS+30EB (70% subsoil = TS + 30% bovine manure = EB); SC (commercial substrate); S100TS (100% TS); S70TS+30CCB (70% TS + 30% Compost Barn Bed = CCB) and S50TS+50CCB (50% TS + 50% CCB). Seedling evaluations were performed at 60 days after sowing. The micrometeorological data were obtained by means of automatic and direct reading sensors in the greenhouse. For the external environment, the data were obtained from an automatic station and a direct reading sensor. There was an interaction effect (Concentrations x Substrates) for most of the agronomic variables, providing an increase in plant development. The temperature, relative humidity and solar radiation showed a strong linear correlation between the evaluated environments. Therefore, it was possible to conclude that the production of yellow passion-fruit seedlings is influenced by irrigation with different concentrations of treated domestic wastewater and substrates, resulting in greater morphological growth of the plants. The linear regression models enable the estimation of micrometeorological variables for the conditions evaluated.